PENGARUH MOTIVASI, PERSEPSI DAN SIKAP TERHADAP KEPUTUSAN PEMBELIAN KEMBALI PRODUK EIGER DI KOTA MALANG - Rizky Ardian Jaya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
Abstract: The purpose of this study examines the effect of motivation, perception and attitude on the decision to repurchase Eiger products in Malang. The population in this study are consumers who buy back Eiger products at PT. Eigerindo Multi Product Industri Jl. Soekarno Hatta No. 9A, Malang until December 2019. Because the number is not known with certainty, the population in this study included in the infinite population category. Determination of the number of samples developed by Roscoe in Sugiyono (2015; 131) is Roscoe's theory that the size of the sample that is feasible in research is 30-500 if the sample is divided into categories of the number of sample members per category, then the number of sample members for each category is at least 30. If in the study will conduct a multivariate analysis (correlation or multiple regression), then the number of sample members is at least 10 times the variable studied. Based on Roscoe's theory, the number of research samples is 97 respondents. Sampling is done by non-probability sampling where all populations do not have the same opportunity or opportunity to become a sample member. The analysis used multiple regression. The results showed that the F value of 14.265 with Sig. F is 0,000 and Sig. F is smaller than alpha (α) by 5% (0.05). This means that motivation, perception, and attitude are appropriate to explain the decision to buy back Eiger products in Malang. Motivational variables motivational influence on the decision to buy back Eiger products in Malang. Perception variable influences the decision to repurchase Eiger products in Malang. Attitude variable influences the decision to repurchase Eiger products in Malang.Keywords: motivation, perception, attitude and repurchase decision